The economics of oral health and health care - Birch, Stephen; Listl, Stefan (MEA discussion papers, 2015)
This paper describes the principles of economics and their application to oral health and health care. After illustrating the economic determinants of oral health, the demand for oral health care is discussed with particular reference to asymmetric information between patient and provider. The reasons for the market failure in (oral) health care and its implications for efficiency and equity are explained. Moreover, it is described how economic evaluation can be used to maximize oral health gains in scenarios of scarce resources. The behavioural aspects of patients' demand for and dental professionals' provision of oral health services are discussed. Finally, methods for an optimized planning of the dental workforce are discussed
Nach Informationen von SSRN wurde die ursprüngliche Fassung des Dokuments May 20, 2015 erstellt